A qualitative survey of factors shaping the role of a safety professional. (October 2022) - Van Wassenhove, Wim; Foussard, Christian; Dekker, Sidney W.A.; Provan, David J.
Highlights: This article presents the results of a project that conducts empirical research into the practice and role of the safety professionals. Blending of theoretical categories of factors that influence the role of a safety professional with a role theory was used as a general analysis frame. This work presents several findings: (1) the factors identified by Provan et al. (2017) can be associated to a theoretical model of factors involved in the taking of organizational roles by the safety professionals. (2) We can also identify those 25 factors in real professional contexts, these factors are pertinent and relevant for safety professionals. (3) The 25 factors are not independent, some of them are reciprocal related and some of them have dependencies. Those relationships can give light on how roles of safety professionals are socially constructed. Abstract: Provan et al (2017) conducted a systematic literature review in Safety Science that included more than 100 publications of the last 30 years published on the role of the safety professional. This comprehensive review identified 25 factors that shape and influence the role of the safety professional. These factors are organized in three categories: institutional, relational, and individual. The review highlighted a dearth of empirical research into the practice and role of the safety professionals. This article presents the results of a project combining two objectives: (1) conduct empirical research into the practice and role of the safety professionals; (2) support the reflection by safety students about their future role in organizations and the factors that will influence that role. The main contribution of this paper consists in delivering empirical data from a research setup that helped students to understand more clearly their role as (future) safety professionals. This is achieved through getting the students themselves engage with Provan's work and do interviews with practicing safety professionals using Provan's categories as inspiration for interview questions and discussion topics. The blending of Provan's categories of factors with a role theory was used as a general analysis frame. This work presents several findings: (1) the factors identified by Provan et al. (2017) can be associated to a theoretical model of factors involved in the taking of organizational roles by the safety professionals. (2) We can also identify those 25 factors in real professional contexts, these factors are pertinent and relevant for safety professionals. (3) The 25 factors are not independent, some of them are reciprocal related and some of them have dependencies. Those relationships can give light on how roles of safety professionals are socially constructed. Reflection on those factors is very useful for future safety professionals (the students), this appeared to be an effective pedagogic process that enhance the processes of professional socialization of future safety professionals (Foussard et al., 2021 ). However, this last point will not be discussed in this paper.